THE USE OF FINE SEDIMENT FRACTAL DIMENSIONS AND COLOUR TO DETERMINE SEDIMENT SOURCES IN A SMALL WATERSHED - Krein A.; Petticrew E.; Udelhoven T. (My University, 2003)
As many particle-associated contaminants and nutrients are supply controlled, the question of particle source is crucial. In addition, sediment storage has important implications for the delivery and fate of pollutants. Increased accumulations of fine sediment (<63 μm) in gravel beds not only modify benthic habitat but also increase the retention time of sediment-associated contaminants in these biologically active areas of river systems. It is of overriding importance to determine the origin of the fines and the amount, location and process of storage. There is little doubt that the characteristics of particles can be used to derive this information. There is no general agreement, however, about the characteristics that should be considered in such investigations. Furthermore, scientists have a great demand for simple methods, especially for routine use under dry weather conditions when suspended particle concentrations are low. This investigation shows that, in addition to loss on ignition, the determination of fractal dimension and particle colour also provide a fast and easy approach. After filtering the suspensions through glass microfibre filters, the dried filter residues are scanned by a colour scanner. Particle-bound cations and heavy metals were analysed by atomic absorption spectrometry after material decomposition with nitric acid. Fractal dimensions were obtained from measurement of the digital pictures using standard methods of digital image analysis. The fractal dimension decreases, indicating an increase in the regularity of particle morphology as one moves from gravel-stored sediment to surface-stored sediment to suspended sediment. Generally, flocs with high organic content exhibit more irregular morphology while single mineral particles have a more regular shape. In this study, the dominant factor for variable particle morphology was determined to be the mechanical forces influencing the flocs. An increase in shear associated with high flows and the impact of colliding with the channel bed appears to result in less flocculated, more regular particles at the surface. In addition, the morphology of particles shows that the exchange of particles in the gravel bed takes place during and shortly after flood events when the armoured layer is broken up and the sediment down to a depth of several centimetres is disturbed. Deposition onto the sediment surface was observed during the falling limb of every event. Surface sediment and suspended sediment show similarities in loss on ignition and particle morphology, particularly in low flow conditions when the stored amount of 25 mg/cm2 is not exceeded. The exchange between suspended sediment sources over the course of a year can be described using colour variation of the fine sediment. Along with particle-bound manganese, it can be shown that during both the winter month, which exhibit a high baseflow, and flood events, distant sediment sources predominate. In summer low flow conditions, in-channel sources are more important. Furthermore, the use of colour values can allow prediction of the sediment chemical properties as, for example a significant linear correlation between particle colour and particle-bound manganese was found.
Keywords: Gravel bed river; Fine sediment; In-channel storage; Fractal dimension; Particle colour